LIPID PRODUCING MICROALGAE FROM SEVERAL ECOSYSTEMS IN WEST AND CENTRAL JAVA, INDONESIA - DWI ANDREAS SANTOSA; SULASTRI (SEAMEO BIOTROP, 2010)
This study is aimed to get lipid producing microalgae as feedstock for biofuel production. The microalgae were isolated from 355 collected water samples which represented many distinct ecosystems such as paddy fields, rivers, agricultural dams, ponds, swampy areas and unique ecosystem of volcano and mud-volcano craters in West- and Central Java, Indonesia. A total of 267 strains of microalgae were isolated from the samples of which 221 strains of them have capability to produce lipid. There were four promising strains that produce lipid between 14.7 – 45.7 percent dry weight in optimal condition that were identified as Chlamydomonas sp. KO-7267 and PK-7195, Chlorella sp. KS-7300 and Desmodesmus sp. BK-7291. Keywords: microalgae, lipid, biofuel, Indonesian ecosystems